Acute treatment of headache - Rapoport, A. M. (Springer-Verlag, 2006)
Effective acute treatment of headache begins with making an accurate diagnosis and ruling out secondary causes of headache. Once a primary headache is diagnosed, it is important to choose the right combination of behavioural therapy and acute care (abortive and symptomatic) therapy for each patient. Some patients may need preventive medication on a daily basis. If patients overuse acute medications and develop medication overuse headache (previously called analgesic rebound headache), they often seek medical attention due to the chronicity and/or intensity of their pain and resultant disability. For acute care of migraine, physicians should choose a triptan they know and expect to work. They should prescribe the dose and route of administration that will provide the most rapid and complete response to all the associated symptoms of migraine, in addition to the pain. The effectiveness of the 7 available triptans in early, double-blind, controlled trials is more similar than different. How and when to give them will be discussed. Treatment of cluster headache will be presented briefly.